2022
DOI: 10.1002/ctm2.693
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA‐204‐5p inhibits APJ signalling and confers resistance to cardiac hypertrophy and dysfunction

Abstract: Background MicroRNAs regulate cardiac hypertrophy development, which precedes and predicts the risk of heart failure. microRNA‐204‐5p (miR‐204) is well expressed in cardiomyocytes, but its role in developing cardiac hypertrophy and cardiac dysfunction (CH/CD) remains poorly understood. Methods: We performed RNA‐sequencing, echocardiographic, and molecular/morphometric analysis of the heart of mice lacking or overexpressing miR‐204 five weeks after trans‐aortic constriction (TAC). The neonatal rat cardiomyocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 82 publications
(99 reference statements)
1
8
0
Order By: Relevance
“… 33 miR-204 is highly expressed in vascular endothelial cells, 33 , 64 pancreatic β-cells, 97 , 98 and cardiomyocytes. 101 The inhibition or genetic deletion of miR-204 improves endothelial function and glycemic control despite obesity in the genetically diabetic db / db mice. 33 , 99 Castaño et al reported that the systemic administration of serum exosomes isolated from obese mice overexpressed miR-122 and promoted obesity and glucose intolerance in the lean mice by regulating PPAR-α in the epididymal white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“… 33 miR-204 is highly expressed in vascular endothelial cells, 33 , 64 pancreatic β-cells, 97 , 98 and cardiomyocytes. 101 The inhibition or genetic deletion of miR-204 improves endothelial function and glycemic control despite obesity in the genetically diabetic db / db mice. 33 , 99 Castaño et al reported that the systemic administration of serum exosomes isolated from obese mice overexpressed miR-122 and promoted obesity and glucose intolerance in the lean mice by regulating PPAR-α in the epididymal white adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, their role in endocytosis and intracellular trafficking remains largely unknown. Over the past decade, research on miRNAs has shown their involvement in endocytosis processes [ 103 , 104 , 105 ]. For instance, the miR-199 family (miR-199a-5p and miR-199b-5p) markedly regulates the expression of endocytosis mediators such as clathrin heavy chain (CLTC), Rab5A, LDLR, and caveolin-1 [ 103 ].…”
Section: Implications Of Mirnas In Endocytosis Process Regulationmentioning
confidence: 99%
“…However, it is unknown whether altered expression of these proteins by miRNAs affects their endocytosis and contributes to the observed phenotype. We recently reported that miR-204 promotes APJ (apelin-receptor) endocytosis via a dynamin-independent, calcium-dependent mechanism and confers protection against cardiac hypertrophy and dysfunction [ 104 ]. Others have also reported that miR-regulated calcium-mediated receptor endocytosis is involved in maintaining neuronal synaptic plasticity.…”
Section: Implications Of Mirnas In Endocytosis Process Regulationmentioning
confidence: 99%
See 2 more Smart Citations